Multi-authority ABS supporting dendritic access structure - MO, Ruo (Institutional Knowledge at Singapore Management University, 2017)
Attribute-based signature (ABS), which could realize fine-grained access control, was considered to be an importantmethod for anonymous authentication in cloud computing. However, normal ABS only provided simple accesscontrol through threshold structure and thus could not cope with the large-scale attribute sets of users in the cloud. Moreover,the attribute sets were supervised by only one attribute authority, which increased the cost of computation and storage.The whole system was in danger of collapsing once the attribute authority was breached. Aiming at tackling theproblems above, a novel scheme, was proposed called multi-authority ABS supporting dendritic access structure whichsupported any AND, OR and threshold gates and affords more flexible access control. Meanwhile, the attribute sets ofusers were classified by diverse attribute authorities which reduced the overhead and the risk of systems. Besides, thescheme is proved to be selective predicate chosen message attack secure in the random oracle model.